2020
DOI: 10.1186/s13019-020-01370-1
|View full text |Cite
|
Sign up to set email alerts
|

One minute of circulatory arrest for acute type A aortic dissection --------- a simple operation for acute type A aortic dissection (AAAD)

Abstract: Background Sun’s procedure is currently recognized as the standard procedure for acute type A aortic dissection (AAAD). But the operation istoo difficult for beginners. We hope to reduce the difficulty and complications of this operation. Methods The aortic arch was immediately cross-clamped after the stented graft was inserted into the distal aorta. Thereafter, the lower-body perfusion was restored. Then, anastomosis was performed between the proximal stent graft and the distal 4-branched Dacron graft. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…These four branched prostheses facilitate early re-initiation of systemic perfusion through one of the branches, after completion of the distal anastomosis. 42 Some authors have even suggested nearly eliminating CA, as they either clamp the stent graft distally after insertion, 43 or occlude the distal stent using a balloon, 44 leading to significantly fewer renal complications. 45 Moreover, another meta-analysis has suggested axillary artery cannulation to be superior to femoral cannulation, in terms of mortality and neurological complications.…”
Section: Circulatory Arrest and Cerebral Protectionmentioning
confidence: 99%
“…These four branched prostheses facilitate early re-initiation of systemic perfusion through one of the branches, after completion of the distal anastomosis. 42 Some authors have even suggested nearly eliminating CA, as they either clamp the stent graft distally after insertion, 43 or occlude the distal stent using a balloon, 44 leading to significantly fewer renal complications. 45 Moreover, another meta-analysis has suggested axillary artery cannulation to be superior to femoral cannulation, in terms of mortality and neurological complications.…”
Section: Circulatory Arrest and Cerebral Protectionmentioning
confidence: 99%
“…Intraoperative cryogenic extracorporeal circulation, the longer will likely affect kidney blood supply, increase renal ischemia hypoxia, cause kidney damage, plus the extracorporeal circulation leads to the activation of systemic inflammation factors, a systemic inflammatory response syndrome, thus appeared the body each viscera, the damage to the organization, and ischemia, corresponding viscera function is not complete. Secondly, the turnaround time of CPB is under the condition of deep and low temperature, and the coagulation balance of the whole body is broken, which further aggravates the burden of kidney and causes AKI [ 24 ]. In this study, suspended red blood cell infusion was an independent risk factor for postoperative AKI in overweight ATAAD patients ( P = 0.015).…”
Section: Discussionmentioning
confidence: 99%
“…The conventional Sun's surgical method uses unilateral cerebral perfusion by CPB to maintain the perfusion of the brain, and the reconstruction of arch branches must be performed under CPB 4 . Although the other arch-first technique before us ensured the cerebral perfusion or reduced time, they were still performed under CPB [8][9][10][11] .…”
Section: Discussionmentioning
confidence: 99%